EFFICACY AND SAFETY OF ALENDRONIC ACID IN PATIENTS WITH JUVENILE RHEUMATOID ARTHRITIS AND OSTEOPOROSIS - A.O. Lisitsin; E.I. Alexeeva; V.G. Pinelis; M.I. Bakanov; S.I. Valieva; T.M. Bzarova; K.B. Isaeva; G.V. Kuznetsova; E.N. Arsen'eva; R.V. Denisova (Union of pediatricians of Russia, 2010)
Search for and practical application of new medications to treat of osteoporosis is one of the critical issues in pediatric rheumatology. The article reviews the efficacy and safety of alendronic acid in 64 subjects with juvenile rheumatoid arthritis and systemic osteoporosis. It is demonstrated that alendronate-based therapy in weekly 1 mg/kg doses over 12 months facilitated reliably increased bonedensity, decreased intensity of pain syndrome, and lowered C-terminal telopeptide serum concentration, which indicates improved bone metabolism processes.Key words: juvenile rheumatoid arthritis, osteoporosis, children, treatment, bisphosphonates, alendronic acid. (Pediatric Pharmacology. - 2010; 7(1):48-54)